Degradace izolačních materiálů vlivem cizích částic - Hoferek, Jiří (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2018)
Práce je věnována vlivu prachových částic na chod točivých strojů s kluzným kontaktem. V práci jsou popsány a charakterizovány prachové částice z prostředí vybraných strojů. Je zkoumán jejich vliv na chod kluzného kontaktu a vliv na izolační systém těchto strojů.

The work is devoted to the influence of dust particles on the operation of rotating machines with sliding contact. In the work are described and characterized dust particles from environment of selected machines. Their influence on sliding contact and influence on the insulation system of these machines is investigated.
Degradation of insulating materials due to foreign particles
Keywords: prachová částice; kluzný kontakt; izolace; dust particles; sliding contact; insulation